PENGARUH AIR SEDUHAN KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP KELARUTAN ION KALSIUM GIGI PERMANEN ( in Vitro) - Nurilawaty, Vitri; Hanum, Nur Adiba; Wahyuni, Sri (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2013)
Email destruction is mainly due to the demineralization of mineral hydroxy apatite enamel due to chemical processes. Demineralization occurs when the pH of the mouth below the critical point (pH <5.5), due to the acidic conditions in the oral cavity, such as the consumption of fruit juices, alcoholic beverages and soft drinks. One plant can prevent many diseases is Rosella (Hibiscus sabdariffa L.). Rosella flower contain the high of citric and malic acid. The purposes of this study is to determine the effect of steeping water rosella flower on the solubility of calcium ions in permanent teeth. The samples are 25 permanent maxillary premolars free of caries, divided into 5 groups. Each group were immersed in roselle calyx infusion of 1%, 2%, 4%, distilled water and soft drinks. The long immersion in roselle water for 3.5 days. The measurement of calcium levels regardless of the email using Atomic Absorption Spectrophotometer. The results showed that there were significant differences betweenthe concentrations of roselle infusion in permanent teeth dissolves the calcium ion. Levels of the solubility of calcium ions permanent teeth are soaked in water 1% rosella flower infusion of 128.7 ppm, 2% infusion of 94.5 ppm, 4% infusion of 54.2 ppm. The research conclusions are steeping water rosella flowers have a significant effect in dissolving the calcium ion of the permanent teeth. The higher concentration of steeping rosella flowers was soluble the lower levels the ion calcium in permanent teeth.